DAMPAK KEBERADAAN TAMAN WISATA ALAM MAYANG TERHADAP EKONOMI MASYARAKAT DI SEKITARNYA - ", Nurlaili; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Taman Alam Mayang Pekanbaru. The purpose of this research is to know how many local workers working in Taman Alam Mayang and how many job opportunities exist in the vicinity, knowing the contribution of Alam Mayang Tourism Park to the socio-economic Community Public perception of Taman Alam Mayang. The topic of focus of this research is the contribution of Taman Wisata Alam Mayang to the socio-economic surrounding community. The samples in this study amounted to 50 people. The authors use quantitative methods and use simple random sampling techniques. Data instruments are observations, polls and documentation. From the research conducted, the authors found that 98% of Alam Mayang's parks hired the surrounding community. For working time, 98% of respondents also said that there is no authority in employee work time. Employee working hours as stipulated by the park organizer Alam Mayang. 44% of respondents stated that Alam Mayang Tourism Park is a good contribution to the economically incapacitated community. 44% of respondents stated that Alam Mayang Tourism Park provides assistance to the community. 92% of respondents stated that Alam Mayang Tourism Park has never contributed to the preservation of the environment around the tourist attractions. 84% of respondents stated that Taman Alam Mayang is always showing the character of Riau Malay culture. The research also found that public perception of nature park activities is positive. It is known from the 84% respondent response score that has received positive benefits from Taman Alam Mayang tourism activities. Keywords: social perception, socio-economics